The actn3 r577x nonsense allele is under-represented in elite-level japanese endurance runners - Saito, D.; Fuku, N.; Mikami, E.; Kawahara, T.; Tanaka, H.; Higuchi, M.; Tanaka, M. (Japanese Journal of Physical Fitness and Sports Medicine, 2011)
Although previous reports have shown a lower proportion of the ACTN3 XX genotype (R577X nonsense polymorphism) in sprint/power athletes compared with controls, possibly attributed to the importance of skeletal muscle function associated with alpha-actinin-3 deficiency, the findings on association between endurance athlete status and R577X genotype are equivocal. Purpose: The present study was undertaken to examine association of ACTN3 R577X genotype with elite Japanese endurance athlete status. Subjects and Methods: Subjects comprised 79 elite Japanese endurance runners (E) who participated in competition at national level and 96 Japanese controls (C). We divided endurance runners into two groups, i.e., 42 national level runners (E-N) and 37 international level runners (E-I) who had represented Japan in international competition. R577X genotype (rs1815739) was analyzed by direct sequencing. Frequency differences of polymorphisms between athletes and controls were examined by Chi-square tests. Result: The R allele frequency tended to be higher in E group than in C group (P=0.066). When we divided E into two groups, the R allele frequency in E-I group was significantly higher than that in C group (P=0.046); whereas there were no significant differences between E-N and C groups (p=0.316). Then, the three genetic models were tested. In the additive genetic model (RR>RX>XX), there were significantly differences between E-I and C (P=0.038), but not the dominant (RR vs. RX+XX) and the recessive (RR+RX vs. XX) genetic models. Conclusion: R allele of the R577X genotype in the ACTN3 gene was associated with elite Japanese endurance athlete status